Peculiarities of the course of dipylidiosis in dogs depending on the intensity of infestation - Nikitan, A.; Melnychuk, V. (Scientific Progress & Innovations, 2024)
Dipylidiosis is a common disease among domestic dogs and cats, caused by the cestode Dipylidium caninum (Linnaeus, 1758). Infestation of animals occurs through alimentary means – when adult fleas or hair-eaters are swallowed, which contain the cysticercoid stage of the parasite. Further development of the helminth takes place in the small intestine of the animal, where the causative agent develops to the imaginal stage. From the moment they enter the animal's body until the formation of the sexually mature stage, cestodes have a negative effect on the host in which they live and develop. Clinical signs of the disease are usually uncharacteristic, and their severity may depend on many factors, one of which is the intensity of the invasion. Therefore, the goal of our work was to determine the clinical signs of dipylidiosis in dogs, taking into account the indicators of the intensity of the invasion. The work on the determination of clinical signs in dogs with different degrees of dipilidiosic infestation was performed in the conditions of the Veterinary Clinic “Aibolyt” (Poltava) and the Laboratory of Parasitology of the Poltava State Agrarian University. For the experiment, 3 groups of dogs spontaneously infested with the causative agent of dipylidiosis were formed, with different degrees of intensity of invasion. The first group – animals with a low intensity of invasion (up to 2 cocoons in 1 g of feces), the second – animals with an average intensity of invasion (from 3 to 7 cocoons in 1 g of feces), the third – animals with a high intensity of invasion (from 8 cocoons in 1 g feces). Studies have established that the degree of intensity of dipilidiosic invasion directly affected the manifestation of clinical signs. It was determined that with low intensity of invasion in most cases, the course of the disease was asymptomatic, and only in some dogs was observed a decrease in appetite (25 % of cases), as well as signs of hypodynamia and anemia of visible mucous membranes (12.5 % of cases). At an average degree of intensity of dipilidiosic invasion, the most characteristic and pronounced clinical signs in dogs were: decreased appetite, hypodynamia, diarrhea and tachypnea (from 40 to 50 % of cases); vomiting and anemia of visible mucous membranes (in 30 % of cases). At a high degree of intensity of dipilidiosic infestation in dogs, clinical signs were recorded, indicating deep and complex pathological changes in the body. Characteristic clinical signs were: decreased appetite, hypodynamia, vomiting and diarrhea (100 % of cases); tachycardia and arrhythmia, tachypnea, as well as anorexia (83.3 % of cases); anemia of visible mucous membranes, itching, appearance of alopecia on the skin, cachexia, cyanosis of visible mucous membranes and convulsions (from 50 to 66.6 % of cases).